2009
DOI: 10.1111/j.1399-3054.2009.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungi enhance nitrogen and phosphorus nutrition of Nothofagus dombeyi under drought conditions by regulating assimilative enzyme activities

Abstract: Drought stress conditions (DC) reduce plant growth and nutrition, restraining the sustainable reestablishment of Nothofagus dombeyi in temperate south Chilean forest ecosystems. Ectomycorrhizal symbioses have been documented to enhance plant nitrogen (N) and phosphorus (P) uptake under drought, but the regulation of involved assimilative enzymes remains unclear. We studied 1-year-old N. dombeyi (Mirb.) Oerst. plants in association with the ectomycorrhizal fungi Pisolithus tinctorius (Pers.) Coker & Couch. and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…So far, AM-induced tolerance has been shown to be involved in the enhanced tolerance to drought, high salinity, chemical pollution and oxidative stress, among others, in numerous plants (Bressano et al 2010;Debiane et al 2009;Latef and He 2011;Porras-Soriano et al 2009). The mechanisms underlying the protective roles of AM are ascribed to alleviation of oxidative stress (Debiane et al 2009;Bressano et al 2010;Latef and He 2011), stimulation of water uptake and/or nutrient absorption (Alvarez et al 2009;Cho et al 2009;Porras-Soriano et al 2009), modification of root system structure (Yao et al 2009) and change of transcript levels of genes involved in signaling pathway or stress response (Porcel et al 2006;López-Ráez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…So far, AM-induced tolerance has been shown to be involved in the enhanced tolerance to drought, high salinity, chemical pollution and oxidative stress, among others, in numerous plants (Bressano et al 2010;Debiane et al 2009;Latef and He 2011;Porras-Soriano et al 2009). The mechanisms underlying the protective roles of AM are ascribed to alleviation of oxidative stress (Debiane et al 2009;Bressano et al 2010;Latef and He 2011), stimulation of water uptake and/or nutrient absorption (Alvarez et al 2009;Cho et al 2009;Porras-Soriano et al 2009), modification of root system structure (Yao et al 2009) and change of transcript levels of genes involved in signaling pathway or stress response (Porcel et al 2006;López-Ráez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mycorrhizal fungi are key to tree nutrition ( Alvarez et al, 2009 ; Plassard and Dell, 2010 ; Cairney, 2011 ; Becquer et al, 2014 ; Johri et al, 2015 ). Therefore, an obvious idea is that mycorrhizal diversity might be affected by soil P stocks similar as known for nitrogen ( Lilleskov et al, 2002 ; Cox et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation between ECM symbiosis and plant performance in drought conditions has been reported (Morte et al 2001 ;Dunabeitia et al 2004 ;Alvarez et al 2009 ), although plant response to drought can vary depending on the ECM fungal species (Dosskey et al 1991 ;Kennedy and Peay 2007 ). More recently, a pot experiment, using Pinus sylvestris seedlings inoculated with several ECM fungi ( Cenococcum geophilum , Paxillus involutus , Rhizopogon roseolus , and Suillus granulatus ), has shown that only S. granulatus has a positive effect on shoot growth.…”
Section: Introductionmentioning
confidence: 81%